(untitled) (Journal of Applied and Natural Science, 2018)
In the present study, 21 thermo tolerant tomato (Solanum lycopersicum L.) genotypes were evaluated to delineate the extent of genetic diversity through 10 quantitative traits. The genotypes were categorized into 4 distinct clusters using D2 statistics. Cluster IV had the maximum number (10) of genotypes, where all heat tolerant genotypes grouped together, followed by cluster I (5). Intra cluster analysis revealed that the cluster IV had highest distance, while the inter cluster distance was maximum between cluster III and cluster IV (6.53) indicating the presence of wide range of variability among genotypes of the cluster. Cluster IV recorded maximum cluster mean for yield (579.0), average fruit weight (33.33) and fruit set per cent (54.8) and the cluster III recorded highest mean value for days to 50 percent flowering (67.33). Principal component analysis showed that the first two principal components (PC’s) accounting for 77.6 per cent of total variation. On the basis of inter cluster distance, cluster mean and principal component analysis observed in the present study, a crossing programme involving genotypes from cluster IV will be promising one for developing heat tolerant tomato hybrids.